Monitoring elbow isometric contraction by novel wearable fabric sensing device - Wang, Xi; Tao, Xiaoming; So, Raymond C H; Shu, Lin; Yang, Bao; Li, Ying (Smart materials and structures, 2016)
Fabric-based wearable technology is highly desirable in sports, as it is light, flexible, soft, and comfortable with little interference to normal sport activities. It can provide accurate information on the in situ deformation of muscles in a continuous and wireless manner. During elbow flexion in isometric contraction, upper arm circumference increases with the contraction of elbow flexors, and it is possible to monitor the muscles' contraction by limb circumferential strains. This paper presents a new wireless wearable anthropometric monitoring device made from fabric strain sensors for the human upper arm. The materials, structural design and calibration of the device are presented. Using an isokinetic testing system (Biodex3 ) and the fabric monitoring device simultaneously, in situ measurements were carried out on elbow flexors in isometric contraction mode with ten subjects for a set of positions. Correlations between the measured values of limb circumferential strain and normalized torque were examined, and a linear relationship was found during isometric contraction. The average correlation coefficient between them is 0.938 0.050. This wearable anthropometric device thus provides a useful index, the limb circumferential strain, for upper arm muscle contraction in isometric mode.